Kinderspielzeug von Georgina Beier entworfen (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent)
Copyright exclusively held by Georgina Beier Estate Executor, or jointly by Iwalewahaus, CBCIU. CBCIU and Iwalewahaus identifiers currently unavailable.
Keywords: Art; Women artists; Artists; Playgrounds; Nigeria